(untitled) (Journal on Excellence in College Teaching, 2024)
It is both important and challenging to assess transfer of skills learned through coursework and related organizational and societal contributions. The author describes an action research study to determine the effectiveness of a doctoral course in program evaluation. Using Kirkpatrick’s (Kirkpatrick & Kirkpatrick, 2006) four-level evaluation framework for evaluating training programs, an extended framework by Kaufman, Keller, and Watkins (1995), and adaptations suggested by Praslova (2010), five levels of outcomes were addressed: reaction, learning, transfer, organizational benefit, and societal contributions. Findings evidence positive reactions, learning, transfer, and organizational benefit. Additionally, the study provides implications for others engaged in higher education assessment and evaluation at the course, program, and unit levels.